PERAN GURU SEBAGAI FASILITATOR UNTUK MENUMBUHKAN KETERAMPILAN 4C (CRITICAL THINGKING, CREATIVITY, COMMUNICATION AND COLLABORATION) SISWA KELAS II MELALUI PEMBELAJARAN P5 (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The purpose of this research is to describe the role of the teacher as a facilitator to foster 4C skills and to describe students' 4C skills through P5 learning. This type of research uses a qualitative approach. The data analysis technique used in this research is data collection, data reduction, data presentation and conclusion drawing and verification. The results of the research show that teachers have carried out four indicators of teachers as facilitators well, namely providing learning tools, providing learning facilities by teachers and schools, acting as partners, and not acting arbitrarily. Then students' 4C skills grow, namely creativity, communication and collaboration skills. Meanwhile, students' critical thinking skills are still not growing. However, in this case the teacher continues to make efforts to ensure that students' level of critical thinking continues to grow by conducting questions and answers to students and providing practice questions related to the material.